USE OF CEREAL PRODUCTION TECHNOLOGY IN THE FOOD INDUSTRY (Multidisciplinary Journal of Science and Technology, 2023)
One of them is sorghum. All parts of this plant are of economic value. From sorghum grain, you can get cereals and flour, molasses, starch, syrup, beer and wine. Sorghum is a raw material for the production of ethyl alcohol, cellulose, paper, cardboard, brushes and brooms. Grain is a good concentrated feed for all kinds of animals and birds, green leaves and stems are used for livestock feed in fresh form and are well siloed.